CAN ACCOUNTING INSTRUCTION BE AUTOMATED? - Gordon, Dennis (The Accounting Review, 1962)
Abstract The article discusses the implications of programmed learning and teaching machines in the field of accounting education. Programmed learning appears to be most useful in teaching fundamental concepts and definitions, basic techniques such as journalizing and posting, analysis of financial statements by means of ratios, analysis of variances in a standard cost system, and similar subjects requiring a knowledge of meaningful facts. The most practical solution to the problem of automatic accounting instruction is first to develop units of material and then fit them into the curriculum. This approach would speed the introduction of automated instruction and would be of tremendous help in teaching basic concepts. Instructors could then use this time for reasoning and analysis to make the learning more stimulating and productive. Teaching would be at a higher professional level. Reducing the cost of programming is one of the major economic problems that must be solved. There is no guarantee that programmed learning will save money or solve the teacher shortage, but if the research experience makes traditional teaching and textbooks more effective, education will gain.